Development of an E-Module for Physical Education, Sports, and Health Learning in Martial Arts (Karate) for High School Students in Fase E. - Martinel Prihastuti; Syahrial Bakhtiar; Nurul Ihsan; Atradinal Atradinal; Septri Septri (JETL (Journal of Education, Teaching and Learning), 2025)
Physical Education (PJOK) develops students' physical and character skills through sports like Karate. However, students struggle to learn basic techniques (Kihon, Kata, Kumite) with conventional methods. A multimedia E-Module was developed to enhance understanding, especially for tech-savvy Generation Z students. This R&D study used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Conducted at SMA Negeri 2 Padang, data was collected via questionnaires, tests, and observations. The E-Module includes videos, images, and audio for interactive learning. The results show that the PJOK Karate Learning E-Module was successfully developed and tested. The E-Module integrates multimedia elements such as images, videos, and audio to facilitate better comprehension of basic Karate techniques. Validity tests yielded high scores in language (91.67%), content (95%), and media (98.33%), while reliability was confirmed with a Cronbach’s Alpha value of 0.638. Practicality assessments from both students and teachers were highly positive, ranging from 84.96% to 100%. Additionally, the E-Module proved highly effective, with student effectiveness scores between 82.32%–85.26% and teacher evaluations ranging from 92%–99%. In conclusion, this study demonstrates that the Karate Learning E-Module is a valid, practical, and effective tool for enhancing students' understanding and performance in Karate. Its multimedia-based approach aligns with the learning preferences of Generation Z, making it a valuable resource for modern PJOK education